Microstructural study of microwave sintered zirconia for dental applications. Issue 1 (January 2015) - Monaco, C.; Prete, F.; Leonelli, C.; Esposito, L.; Tucci, A.
Abstract: Conventional sintering techniques for zirconia-based materials, which are commonly used in dental reconstruction, may not provide uniform heating, with the consequent generation of microstructural flaws in the final component. A sintering system using microwave heating may represent a viable alternative. The purpose of this study was to compare the dimensional variation and physical and microstructural characteristics of commercial zirconia (Y-TZP), used as a dental restoration material, sintered in conventional and microwave furnaces. A physical-mineralogical-microstructural characterisation was carried out to evaluate the level of densification and the presence of flaws in the sintered specimens. Use of the microwave systems allowed the length of the sintering cycle to be reduced to a few minutes, compared with the several hours necessary with a 'traditional' heating system. Additionally, the maximum temperature used to reach the required density decreased from 1450–1480 °C with the electric furnace to 1200 °C in the microwave furnace. An important clinical implication is that the reduced sintering time could allow the introduction of zirconia in chair-side treatments, if used as a monolithic material.